2019
DOI: 10.1002/celc.201900376
|View full text |Cite
|
Sign up to set email alerts
|

Mn3O4@NC Composite Nanorods as a Cathode for Rechargeable Aqueous Zn‐Ion Batteries

Abstract: Rechargeable aqueous zinc-ion batteries (ZIBs) have attracted escalating attention recently, owing to their energy density, decreasing cost, advanced safety, and environmental benignity. Nevertheless, ZIBs still lack suitable cathode materials with stable cycling performance, owing to the high polarization of zinc ion. Therefore, developing candidate materials with excellent properties remains a great challenge. Herein, we successfully synthesize a novel Mn 3 O 4 @N-doped carbon matrix composite nanorods (Mn 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(35 citation statements)
references
References 52 publications
0
35
0
Order By: Relevance
“…[27] In addition, structurale ngineering of electrode materials is an effective method to improve their electrochemical activity and kinetics. [33][34][35] For instance, Liu and co-workerss ynthesized Mn 3 O 4 nanorods coated with nitrogen-doped carbon matrix, which delivered high reversible capacity of 97.0 mAh g À1 at 1.0 Ag À1 after 700 cycles. [33] The improved electrochemical performance was attributed to the nitrogen-doped carbon shell and the synergetic effect of Zn 2 + and Mn 2 + in the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] In addition, structurale ngineering of electrode materials is an effective method to improve their electrochemical activity and kinetics. [33][34][35] For instance, Liu and co-workerss ynthesized Mn 3 O 4 nanorods coated with nitrogen-doped carbon matrix, which delivered high reversible capacity of 97.0 mAh g À1 at 1.0 Ag À1 after 700 cycles. [33] The improved electrochemical performance was attributed to the nitrogen-doped carbon shell and the synergetic effect of Zn 2 + and Mn 2 + in the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] For instance, Liu and co-workerss ynthesized Mn 3 O 4 nanorods coated with nitrogen-doped carbon matrix, which delivered high reversible capacity of 97.0 mAh g À1 at 1.0 Ag À1 after 700 cycles. [33] The improved electrochemical performance was attributed to the nitrogen-doped carbon shell and the synergetic effect of Zn 2 + and Mn 2 + in the electrolyte. Chen and co-workers reported the construction of cation defects in spinel ZnMn 2 O 4 ,w hichg reatlyi mprovedt he cycling stabilitya nd resulted in ad ischarge capacity of 150.0 mAh g À1 at 0.5 Ag À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the nature of the reaction mechanisms involved is still under debate and large‐scale electrodes are yet to be demonstrated, this approach appears to overcome cycling issues related to the alkaline version of the Zn/MnO 2 battery 16‐24 . Among different manganese oxide phases that are reported for near‐neutral batteries, it was discovered that even oxides with lower oxidation states, like Mn 3 O 4 and Mn 2 O 3 , have some activity in this regard 25‐28 . Little attention has been given to the activation mechanism and processes that lead to capacity increase in these phases.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24] Among different manganese oxide phases that are reported for near-neutral batteries, it was discovered that even oxides with lower oxidation states, like Mn 3 O 4 and Mn 2 O 3 , have some activity in this regard. [25][26][27][28] Little attention has been given to the activation mechanism and processes that lead to capacity increase in these phases. The only study in this respect has been that of Zhang et al, 26 which concluded that that Mn 3 O 4 is transforming to the birnessite phase of MnO 2 during charging and after many activation cycles, while discharge capacity originates from zinc intercalation into the birnessite phase.…”
mentioning
confidence: 99%
“…Notably, such layered host structures can realize an efficient transport kinetics by regulating the interlayer environments. While for nonlayered one, many types of materials also have been reported previously, such as the olivine‐type (LiFePO 4 ) [ 82 ] and spinel‐type (ZnMn 2 O 4 , [ 83 ] Mn 3 O 4 , [ 84 ] and Co 3 O 4 [ 85 ] ) host structures. Among them, the spinel‐type cathode materials usually possess a relatively high operating voltage, but a poor structural stability owing to the thermodynamic instability of phase transition during cycling.…”
Section: An Overview Of Cathode Materialsmentioning
confidence: 99%